Jatrophacine, a 4, 5-seco-rhamnofolane diterpenoid with potent anti-inflammatory activity from Jatropha curcas. Issue 16 (12th August 2021) - Hu, Yang; Zhao, Huimin; Yang, Aiping; Lv, Qi; Ding, Ning; Lu, Tu-Lin; Hu, Lihong; Wang, Xiachang
Abstract: A new diterpenoid named jatrophacine (1 ), with an unusual 4, 5- seco - rhamnofolane skeleton, was isolated from the roots of Jatropha curcas, together with eleven known diterpenoids. The structure of the new compound was elucidated through a detailed analysis of its 1 D- and 2 D-NMR spectra. The X-ray structure of jatrophol (2 ) is also presented. Anti-inflammatory activity with LPS-induced RAW 264.7 macrophages revealed that compound 1 strongly inhibited the production of nitric oxide (IC50 = 0.53 μM). GRAPHICAL ABSTRACT: